Temporal trends in right heart strain in patients undergoing pulmonary thromboendarterectomy for chronic thromboembolic pulmonary hypertension. Issue 11 (7th November 2021) - Peters, Andrew C.; Madhan, Ashwin Shaan; Kislitsina, Olga; Elenbaas, Christian; Nishtala, Arvind; Freed, Benjamin; Schimmel, Daniel; Thomas, James D.; Cuttica, Michael; Malaisrie, S. Christopher
Abstract: Background: Pulmonary thromboendarterectomy (PTE) is a curative procedure for chronic thromboembolic pulmonary hypertension (CTEPH). Right ventricular free wall strain (RV FWS) and right atrial strain (RAS) are not well studied in a CTEPH population. We sought to determine temporal trends in RAS and RV FWS in patients post‐PTE. Methods: 28 patients undergoing PTE for CTEPH were prospectively enrolled in a surgical database. Comprehensive echocardiographic assessment of the right heart was performed including RV FWS, right atrial volume, and the three components of RAS: reservoir, conduit, and booster strain. Results: Patients undergoing PTE demonstrated improvement in NYHA functional class ( P  < 0.001). Hemodynamic assessment showed improvement in mean pulmonary artery pressure from 49.7 ± 8.5 mm Hg to 23.9 ± 6.5 mm Hg ( P  < 0.001) and pulmonary vascular resistance decreased from 7.8 ± 3.2 wu to 2.4 ± 1.3 wu ( P  < 0.001). Tricuspid annular plane systolic excursion (TAPSE) and lateral S` declined immediately post‐op. RV FWS improved from −14.4 ± 4% to −19 ± 3.4% post‐op and −21.2 ± 4.7% at long‐term follow‐up ( P  < 0.001). Improvement in RV FWS post‐op was driven primarily by increases in the apical and mid segments. RA volume declined significantly during the study period. RA reservoir and conduit strain improved after PTE. Conclusion: Patients undergoing PTE for CTEPH had significant improvement in right heart hemodynamics immediately post‐op. Traditional echo metrics of RV performance including TAPSE and lateral S` did not improve. RV FWS improved, which was driven by changes in the apical and mid segments. This highlights that RV FWS is a viable and useful metric to follow in CTEPH patients post‐PTE.